BENEFITS OF FLUTTER FOR SMALL AND MEDIUM BUSINESS MOBILE APP DEVELOPMENT - Shokirov Farrux Shuxrat o’g’li (Лучшие интеллектуальные исследования, 2024)
Abstract: This article discusses the benefits of using Flutter for small and medium business mobile app development. Provides insights into why Flutter is becoming increasingly popular in various industries, including healthcare, finance, and e- commerce.